2007
DOI: 10.3348/kjr.2007.8.1.32
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Breast for the Detection and Assessment of the Size of Ductal Carcinoma in Situ

Abstract: ObjectiveThe aim of the study was to compare the accuracy of magnetic resonance imaging (MRI) and mammography for the detection and assessment of the size of ductal carcinoma in situ (DCIS).Materials and MethodsThe preoperative contrast-enhanced MRI and mammography were analyzed in respect of the detection and assessment of the size of DCIS in 72 patients (age range: 30-67 years, mean age: 47 years). The MRI and mammographic measurements were compared with the histopathologic size with using the Pearson's corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 19 publications
4
26
0
1
Order By: Relevance
“…Proponents of breast MRI argue that MRI better characterizes tumor extent and, as such, should improve surgical planning and decrease the rate of positive surgical resection margins and, therefore, the need for re‐excision. However, studies have demonstrated significant variability in tumor size estimation by MRI, with underestimation reported in 8% to 59% of cases and overestimation in 11% to 70% of cases …”
Section: Introductionmentioning
confidence: 99%
“…Proponents of breast MRI argue that MRI better characterizes tumor extent and, as such, should improve surgical planning and decrease the rate of positive surgical resection margins and, therefore, the need for re‐excision. However, studies have demonstrated significant variability in tumor size estimation by MRI, with underestimation reported in 8% to 59% of cases and overestimation in 11% to 70% of cases …”
Section: Introductionmentioning
confidence: 99%
“…[45678910192021222324252627] In our analysis of women of age 60 years and above undergoing presurgical bilateral breast MRI, we found additional malignancy in 9% of the patients (114/1268). Of these new malignancies, 2.4% were in the contralateral breast.…”
Section: Discussionmentioning
confidence: 83%
“…But median volumes of excised tissue were lower in the MRI group and the authors postulated the higher rate of re-excision was due to surgeons being inappropriately reassured by small lesion size on MRI. This suggests that the sensitivity of MRI in showing extent of in situ disease is less than standard imaging, in contrast to others 28,29 where MRI better depicted the extent of than mammography. A more recent randomised controlled trial (RCT) of 440 women, selected by young age alone 25 found the MRI group had higher BCS planned and a change to mastectomy occurred in 15%, but a lower overall re-operation rate in the MRI group (5% vs. 15%) (P < 0.0001).…”
Section: Mri In Assessing Disease Extent and Guiding Surgerymentioning
confidence: 85%
“…But median volumes of excised tissue were lower in the MRI group and the authors postulated the higher rate of re‐excision was due to surgeons being inappropriately reassured by small lesion size on MRI. This suggests that the sensitivity of MRI in showing extent of in situ disease is less than standard imaging, in contrast to others where MRI better depicted the extent of than mammography.…”
Section: Mri In Assessing Disease Extent and Guiding Surgerymentioning
confidence: 90%